A covalently conjugated branched DNA aptamer cluster-based nanoplatform for efficiently targeted drug delivery. Issue 26 (21st June 2022) - Li, Runze; Wu, Xiaohui; Li, Jing; Lu, Xuehe; Zhao, Robert Chunhua; Liu, Jianbing; Ding, Baoquan
Abstract : A covalently conjugated branched DNA aptamer cluster-based nanoplatform was designed for efficiently targeted drug delivery to inhibit the proliferation of tumor cells. Abstract : Targeted delivery of therapeutic drugs is essential for precise treatment of various diseases to reduce possible serious side-effects. A screened DNA aptamer has been widely developed for active targeting delivery. Herein, we report a facile strategy for the construction of a branched DNA aptamer cluster-based nanoplatform for efficiently targeted drug delivery. In our design, the terminal-modified DNA aptamer can be covalently conjugated to form a branched aptamer cluster by click reaction easily. The branched aptamer cluster-modified DNA tetrahedron (TET) demonstrates highly targeted cellular uptake with the modification of only one site. After loading the chemotherapeutic drug (doxorubicin, DOX), the DNA aptamer cluster-based nanoplatform elicits a remarkable and selective inhibition of tumor cell proliferation by much-enhanced targeted delivery. This covalently conjugated branched DNA aptamer cluster-based nanoplatform provides a new strategy for the development of targeted drug delivery.